Short- and long-term impacts of the National Essential Medicines Policy on drug availability, price, and usage in a deprived rural county in southwestern China: an interrupted time series analysis across 8 years - Xiong, Xuechen; Huo, Zhaohua; Zhou, Shuai; Bai, Ge; He, Shiying; Zhou, Yinan; Jia, Jing; Quan, Jianchao; Luo, Li (Frontiers in Public Health, 2024)
Background: China’s National Essential Medicines Policy (NEMP) has been implemented for over 15 years; yet empirical evidence on its long-term impacts is lacking in remote and rural regions. This study aims to assess the short- and long-term effects of NEMP on the drug availability, price, and usage in a deprived rural county in southwestern China. Methods: A quasi-experimental design was employed, featuring a single-group pre-and-post comparison. We gathered 74,436 procurement records from 2009 to 2016 from drug warehouses of local medical institutions. Pharmaceutical data were analysed quarterly, considering various policy and therapeutic attributes. Drug Price Index was calibrated for retail and wholesale prices of 405 medications. We conducted interrupted time-series analysis to examine the immediate and enduring impacts of NEMP’s initial (commencing in January 2011) and second (starting from December 2015) stages. Results: After NEMP, the number of essential medicines surged by 115 but subsequently faced a steady quarterly decline (-9.1) in township healthcare centres (THCs, primary care). Conversely, county hospitals (secondary care) initially saw a reduction of 40 medicines but later exhibited a steady increase (+4.2 per quarter) up to the second-stage NEMP. Regarding price, THCs encountered abrupt (-26.1%/-15.9% in retail/wholesale price) and sustained (-0.2%/-0.3% per quarter) price drops after NEMP. The immediate price change after NEMP in county hospitals were milder but significant in non-essential medicines, and long-term declines were also observed in all drugs. As for total sales, a significant long-term disparity emerged between THCs (+0.9% per quarter) and county hospitals (+3.3% per quarter). Following the second-stage NEMP, retail prices in county hospitals further decreased, although wholesale prices did not; however, following price upward trends were observed in both THCs and county hospitals. Lastly, the influences of NEMP varied across different therapeutical categories of medicines. Conclusions: NEMP has successfully regulated drug prices in primary and secondary healthcare facilities in remote and rural areas, both short-term and long-term. However, a remarkable disparity in medicine availability and utilization was observed between different levels of facilities over time. Continuous monitoring is essential, with increased attention needed on the uneven impacts of the policy on diverse drugs, facilities, regions, and demographics.